Decentralization in the Public Sector: The Case of the U.K. National Health Service - Arrowsmith, James; Sisson, Keith (Relations industrielles / Industrial Relations, 2002)
SummaryDecentralization has been an important international development in large organizations, including those in the public sector, in recent years. The introduction of self-governing trusts in the U.K. National Health Service in the early 1990s serves as a paradigm case of public sector decentralization, managerialism and marketization. Local managers were able to develop their own employment arrangements in order to improve the recruitment, retention and deployment of labour. This article finds that pay initiatives were subverted by environmental constraints but change proceeded in the organization of working time. The findings have implications beyond the U.K. and health service context, notably the conceptual relevance of the “firm-in-sector” framework and the policy limits and potential of decentralization.